Analisis Peran Komite Sekolah dalam Mendukung Transformasi Team Learning Organisasi Belajar - Sari Prabandari; Cicilia Emita; Bambang Wiyoso; Muhammad Japar; Robinson Situmorang (SAP (Susunan Artikel Pendidikan), 2026)
Schools as learning organizations have the ability to adapt, innovate, and continuously improve the quality of educational services internally and sustainably. Team Learning is one of the disciplines of Learning Organizations that involves the process of aligning and developing team capacity, to produce desired results together, including the school committee as one of its components. Team Learning is about how the team thinks, communicates, and acts as a cohesive unit. This study aims to analyze and evaluate the role of the School Committee in the context of building a school Team Learning as a learning organization. The study used a descriptive quantitative method, by distributing a Likert-scale-based questionnaire to respondents, in order to provide a clear and measurable picture of how effectively the School Committee supports the transformation of team learning in schools as learning organizations. Several aspects studied are the role of the school committee in accordance with the Decree of the Minister of National Education Number 044/U/2002, namely as an advisory agency, supporting agency, controlling agency and mediator, as well as the function of the School Committee in relation to the transformation of schools as team learning.  The research, involving 20 respondents from SDIT Ibnu Sina Jakarta, shows that the school committee has played a significant role in supporting the transformation of team learning into a learning organization. However, several recommendations for future improvement were made.